2018
DOI: 10.1007/s11356-018-2362-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of larvicidal, adulticidal, and anticholinesterase activities of essential oils of Illicium verum Hook. f., Pimenta dioica (L.) Merr., and Myristica fragrans Houtt. against Zika virus vectors

Abstract: Aedes aegypti is the vector responsible for transmitting pathogens that cause various infectious diseases, such as dengue, Zika, yellow fever, and chikungunya, worrying health authorities in the tropics. Due to resistance of mosquitoes to synthetic insecticides, the search for more effective insecticidal agents becomes crucial. The aim of this study was to verify the larvicidal, adulticidal, and anticholinesterase activities of the essential oils of the Illicium verum (EOIV), Pimenta dioica (EOPD), and Myristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 66 publications
2
34
0
Order By: Relevance
“…(Ill.ve EO: 89.8 %). The same percentage of this compound was found in other Ill.ve EOs reported in the literature …”
Section: Resultssupporting
confidence: 88%
“…(Ill.ve EO: 89.8 %). The same percentage of this compound was found in other Ill.ve EOs reported in the literature …”
Section: Resultssupporting
confidence: 88%
“…Formulation development is therefore critical for essential oils to be used effectively and safely as pesticides. A number of studies have demonstrated that a suitable vehicle prolongs the insecticidal effect [51,53,54].…”
Section: Essential Oilsmentioning
confidence: 99%
“…In general, insecticides of synthetic origin inhibit the acetylcholinesterase enzyme activity by binding to its active site resulting in an increase in acetylcholine formation and consequently leading to cell death (Edwards and Tchounwou 2005;Jokanovic and Prostran 2009). Continuous use of insecticides induces some mutations in the active site of acetylcholinesterase enzyme which prevents the binding of insecticide on enzyme-active site and avoids its inactivation, thereby creating resistance among vector species (Naqqash et al 2016;Da Rocha Voris et al 2018). Therefore, there is an urgent requirement for exploring innovative and novel strategies for controlling such harmful vector-borne diseases.…”
Section: Introductionmentioning
confidence: 99%